2021
DOI: 10.1177/10499091211060341
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Quality in Advance Care Planning Documentation: A Survey of Current Methods

Abstract: Background High-quality advance care planning (ACP) documentation facilitates the communication of patients’ wishes as they progress in their disease course and travel between health care settings. No consensus exists regarding evaluation of documentation quality, and diverse strategies for assessing quality have been adopted in clinical ACP studies. Methodology We conducted a literature review in PubMed and via manual search to identify clinical studies that assessed ACP quality or completeness as an outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Gesprächshäufigkeit, Zugänglichkeit der Dokumentation, der Gesprächszeitpunkt, Einbezug von Versorgungsakteur*innen, individuelle Gesundheitsziele bzw. -werte, Behandlungsumfang, Prognose und Versorgung am Lebensende (EOL) wurden bereits als zu beachtende Themen in qualitativ hochwertiger GVP beschrieben [28]. Diese und ggf.…”
Section: Einheitlichkeit Der Genutzten Gvp-dokumenteunclassified
“…Gesprächshäufigkeit, Zugänglichkeit der Dokumentation, der Gesprächszeitpunkt, Einbezug von Versorgungsakteur*innen, individuelle Gesundheitsziele bzw. -werte, Behandlungsumfang, Prognose und Versorgung am Lebensende (EOL) wurden bereits als zu beachtende Themen in qualitativ hochwertiger GVP beschrieben [28]. Diese und ggf.…”
Section: Einheitlichkeit Der Genutzten Gvp-dokumenteunclassified
“…Research 1-4 has shown the importance of doctor-patient-family communication, pointing out that when effective, it results in a more solid relationship and greater trust. 5,6 However, studies 7-9 have found that the quality of this communication has been inadequate on many occasions, negatively impacting satisfaction, especially among critically ill or terminally ill patients in hospitals and their families.…”
Section: Introductionmentioning
confidence: 99%